Use of grape seed extract as a natural antioxidant additive in dry-cured pork neck technology - Libera, Justyna; Kononiuk, Anna; Kęska, Paulina; Wójciak, Karolina (Wydawnictwo Politechniki Łódzkiej, 2018)
The grape seeds, which are the post-production waste of juices and wine production, are a rich source of biologically active compounds. The polyphenol compounds present in seeds can be used in the technology of new products of animal origin as a source of natural antioxidants. The effect of three levels (0.1, 0.2 and 0.5%) 40% (v/v) ethanol extract of grape seed (GSE) quality of dry-cured pork neck was tested. Meat product colour, pH value, water activity, free fatty acid (FFA) content and TBARS index were evaluated. The obtained results indicate that the addition of the extract decreased oxidation intensity dry-cured neck during ripening. The treatment with higher concentrations of extracts showed greater lipid stability than that of the lot with 0.1%. The three levels of GSE extract did not influence pH, water activity and colour significantly. This study indicates that the GSE extract was an effective inhibitor of lipid hydrolysis, and at an additive concentration of at least 0.2% limited the oxidative processes occurring in meats during ripening. Therefore, it may be used in dry-cured pork neck to improve the oxidative stability of meat products for the consumers.
Keywords: grape seed extrac; dry-cured neck; oxidative stability; ekstrakt z pestek winogron; proces suszenia na sucho; stabilność oksydacyjna